The ⁹Be(d, t) nuclear reaction at low deuteron energies - Shlyakhov, N.A. (Вопросы атомной науки и техники, 2013)
Consideration is given to the possibility of describing the experimental data, earlier obtained for angular dependences of cross sections and vector analyzing powers (VAP) of the ⁹Be(d, t₀) reaction induced by vector polarized deuterons of energies between 2.5 and 2.8MeV, within the framework of the distorted wave Born approximation (DWBA), using the "measured" optical potential parameters at input/output channels without additional variations. Pairs of sets of optical potential parameters have been found, which permit simultaneous fits of the main trends in the behavior of angular distributions of cross sections and the VAP for ⁹Be(d, t₀). The direct pickup is demonstrated to be the predominant mechanism of the nuclear reaction occurrence at such low energies. It is possible that the characteristic properties of the direct process at so low energies are determined by the peculiarities of interaction between weakly coupled particles in the area of action of the thresholds of disintegration of the reacting nuclei into their fragments. Розглядається можливiсть опису ранiше знайдених експериментальних даних для кутових залежностей диференцiальних перерiзiвi векторних аналiзуючих здiбностей (ВАЗ) реакцiї ⁹Be(d, t₀), викликаних векторно поляризованими дейтронами з енергiєю 2,52...8 МеВ, в межах борнiвського наближення збурених хвиль (БНЗХ) з використанням "вимiряних" параметрiв оптичних потенцiалiв у вхiдномуi вихiдному каналах без додаткових варiацiй. Знайдено пари наборiв параметрiв оптичних потенцiалiв, що дозволяють одночасно вiдтворити основнi тенденцiї в характерi поведiнки кутових розподiлiв перетинiв i ВАЗ для ⁹Be(d, t₀). Показано, що домiнуючим механiзмом протiкання цих ядерних реакцiй при таких низьких енергiях є пряме пiдхоплення. Можливо, що характернi риси прямого процесу при таких низьких енергiях зумовленi особливостями взаємодiї слабозв’язаних частинок в областi дiї порогiв розвалу ядер, що беруть участь у процесi, на їх фрагменти. Рассматривается возможность описания ранее найденных экспериментальных данных для угловых зависимостей дифференциальных сечений и векторных анализирующих способностей (ВАСП) реакции ⁹Be(d, t₀), вызванных векторно поляризованными дейтронами с энергией 2,52...8 МэВ, в рамках борновского приближения искаженных волн (БПИВ) с использованием "измеренных" параметров оптических потенциалов во входном и выходном каналах без дополнительных вариаций. Найдены пары наборов параметров оптических потенциалов, позволяющие одновременно воспроизвести основные тенденции в характере поведения угловых распределений сечений и ВАСП для ⁹Be(d, t₀). Показано,что доминирующим механизмом протекания этих ядерных реакций при столь низких энергиях является прямой подхват. Возможно, что характерные черты прямого процесса при столь низких энергиях определяются особенностями взаимодействия слабо связанных частиц в области действия порогов развала ядер, участвующих в процессе, на их фрагменты.